Pengaruh Kredit Bermasalah, Likuiditas, dan Inflasi terhadap Profitabilitas Bank BUMN - Khairina Salsa Putri; Winarni; Mirasanti Wahyuni (Jurnal Penelitian Ekonomi Akuntansi, 2023)
This research aims to determine the effect of Non Performing Loan, Liquidity, and Inflation toward Profitability on the State-Owned Bank period 2013 – 2022. In this research the sampling technique used was non probability sampling technique and managed to obtained 4 banks. The data used is secondary data from the annual financial reports of State-Owned Banks. The data analysis model uses the Multiple Linear Regression Model. The data analysis technique uses the F Statistical Test, the t Statistical Test, and the Coefficient of Determination. The results of the analysis show that NPL, LDR, and Inflation simultaneously have a significant effect on Profitability. NPL, LDR, and Inflation partially have a significant effect on Profitability at State-Owned Banks for the 2013 – 2022 period. The limitations of this study are the independent variables and the population used are still limited, so it is hoped that next research can add to the independent variables and the population widely.